Physical Model And Study Of SinglePhase Short Circuit In Networks Connecting Transformer Neutral To Ground In Physical Model And Matlab Software - To‘xtashev Alisher Akmaljon o‘g‘li; Eshquziev Khurshidjon Musajonovich (Genius Journals, 2023)
In the article, the connection of the transformer neutral to the ground in two different ways is considered in a physical model. In these experiments, when the neutral of the transformer is connected in different ways, the change of the short-circuit current in the short-circuited phases, the change of the phase voltages, and the change of the values of the active and inductive resistance are considered in the physical model and the model in the Matlab program
Keywords: Transformer; matlab; neutral effectively connected to earth